Positioning of futsal management company: a case study - Sihabudin, Sihabudin (International research journal of management, IT and social sciences, 2017)
The study aimed at obtaining empirical evidence and find clarity of phenomena and conclusions about the positioning analysis of futsal management companies, a case study in 212, Club House, Central Futsal KCP, and King Hall in East Telukjambe. This research method uses descriptive design and correspondence analysis by distributing questionnaires to respondents containing the positioning statement that was analyzed using the SPSS 16.00 program. There were obtained several conclusions (1) Based on consumer’s perceptions there is one who answers “quite agree” especially on strategic location indicators and more dominant respondents respond to feel “agreed” to all positioning indicators carried out, thereby fostering trust in consumers that can be perceived by consumers of futsal visitors, that each futsal place has its advantages. 212 has advantages in service and gives satisfaction to customers, while it has shortcomings in the economic price strategy. Club House has an advantage in price according to quality and comfort, while it has a lack of a maintained cleanliness strategy. Central Futsal KCP has advantages in the location of sales, while it has a lack of facility strategy. King Hall has an economical price advantage while having a shortage in the sales location strategy.